NILAI KREATIFITAS DAN INOVASI DALAM KEWIRAUSAHAAN - Muhammad Tambrin (Eco-Entrepreneur, 2017)
Successful entrepreneurs require an edge derived from some combination of a creative idea and a superior capacity for execution. The entrepreneur’s creativity may involve an innovation product or a process that changes the existing order. Or entrepreneur may have a unique insight about the course or consequence of an external change. Entrepreneurship is the vehicle that drives creativity and innovation. Innovation creates new demand and entrepreneurship brings the innovation to the market. Innovation is the successful development of competitive edge and as such, is the key to entrepreneurship. Creativity and Innovation are at the heart of the spirit of enterprise. It means striving to perform activities differently or to perform different activities to enable the entrepreneur deliver a unique mix of value. Thus the value of creativity and innovation is to provide a gateway for astute entrepreneurship—actively searching for opportunities to do new things, to do existing things in extraordinary ways. Creativity and Innovation therefore, trigger and propel first-rate entrepreneurship in steering organization activities in whatever new directions are dictated by market conditions and customer preferences, thereby delighting the customers to the benefit of the stakeholders. Innovation also means anticipating the needs of the market, offering additional quality or services, organization efficiently, mastering details, and keeping cost under control.